Comparación del manejo de los reproductores de tilapia roja en pilas de concreto con y sin hapas - Araúz M., Aníbal (Escuela Agrícola Panamericana,Zamorano, 2012)
Araúz, A. 2008. Comparison of the management of red tilapia broodstock in concrete tanks with and without hapas. Graduation Project (Thesis) of the B.S. Program in Agricultural Sciences and Production, Escuela Agrícola Panamericana, Zamorano, Honduras. Tilapia is the most important species for fish culture in Central America and the second most important in Latin America. Tilapia culture is often limited by the lack of quality seed to begin each new production cycle. The objective of this experiment was to compare the management of red tilapia brood stock in concrete tanks with and without hapas. Approximately 6 kg of adult females were stocked in each of four tanks (8.0 × 2.0 × 1.1 m) with a 3:1 female to male proportion. A hapa (7.0 × 1.2 × 1.2 m) was placed in each of two of these tanks. The offspring from the fish in the hapas was removed from incubating female’s mouths weekly. Fry swimming in the water of the tanks without hapas were collected three times per week. The offspring were individually counted to determine the total produced and estimate the number of offspring produced/g of female, number of offspring produced/m2 of tank, number of fry produced/day, and evaluate the growth and survival of the adult fish. All of the adult fish originally stocked in the experiment survived the 42-day trial in spite of the intensive management and frequent weekly handling to which they were submitted. The female fish in tanks without hapas gained an average of 34.6 g in weight during the 42-day experiment while the females in hapas gained 11.2 g on average. The average weekly production of offspring was approximately 4× greater (P 0.05) for the fish held in tanks with hapas compared to the capture of fry from the tanks without hapas. No correlation was found between the number of eggs in each clutch and the weight of the female red tilapia. The use of hapas to manage the adult red tilapia results in a greater production of offspring and has only a minimum effect on the total estimated production costs.